An examination of user costs in relation to smokers using a cessation service based in the UK - Neil Walker; Yaling Yang; Vasiliki Kiparoglou; Subhash Pokhrel; Hayley Robinson; Hugo van Woerden (BMC, 2018)
Abstract Background Smoking cessation services provide support to smokers who desire to quit. Published studies to date have looked at the cost and benefit of service provision but typically focus on clinical trial data. Using routinely collected observational data, this study examined the costs involved in providing a service in terms of average health care expenditure per successful quit attempt in addition to population - level cost-effectiveness measures. Methods Data were analysed from Quit-51 smoking cessation service across five English regions between March 2013 and March 2016 (n = 9116). For each user, costs were estimated in relation to: (i) time spent with advisers; (ii) prescription of pharmacotherapy. The total costs compared against self-reported quit at 12 weeks, which represents the time period for which the service is offered. Cost per quit (CPQ), with 95% confidence interval (CI), was calculated by relating total expenditure to the number of quitters, firstly for the whole dataset and then by subgroups of key categorical variables, namely; gender, age group, the Fagerstrom test for nicotine dependence (FTND) and Index of Multiple Deprivation (IMD). Confidence intervals (CIs) for the mean estimates were derived using a non-parametric bootstrap procedure. Parameters derived from the calculation in relation to treatment were used to estimate potential long-term population outcomes under a scenario where the Quit 51 prescription was rolled out nationally. Results The overall mean CPQ for this sample as estimated at 12 weeks was £403.51 (95% CI = £393.36 to £413.76). The estimated CPQs at this time point were comparable for those aged 12-19 (£423.56, 95% CI = £369.45 to £492.60) and those aged 20-29 (£430.76, 95% CI = £395.95 to £470.56). Differences were also seen in relation to other subgroups considered. The treatment parameters translated to a projected increase of 1.5 quality-adjusted life years (QALYs) per 1000 smokers in the short-term and 23.4 QALYS per 1000 smokers based on a lifetime horizon. Conclusions These figures throw light on service expenditure for each successful quit over the timeframe for which the service is offered in addition to highlighting variability in these costs across different subgroups of the user population.